Death : the final mystery - Fanthorpe, R. Lionel (Hounslow book., 2000)
The greatest human problem is that we are all born in the condemned cell. Money and medical science can extend the human lifespan significantly -- perhaps up to one thousand years via cloning and cryogenics -- but in the end, when the last medical miracle has been exhausted, Death still waits patiently for us. In Death: The Final Mystery, Lionel and Patricia Fanthorpe take their investigative skills to those last moments of life and beyond, exploring such puzzling topics as near-death and out-of-body experiences, reincarnation theories, hypno-regression, and automatic writing and other phenomen.